The nexus between Sudan's refugee policy and its bilateral relations with Ethiopia and Eritrea - Burke, Shelley (AUC Knowledge Fountain, 2013)
This thesis analyzes the impact of Sudan’s bilateral relations with the Eritrean and Ethiopian governments upon its practice of refoulement of asylum-seekers and refugees from those countries. It argues that Sudan uses the asylees from these two states as tools and objects of policy. In different contexts and depending on relations between the states at a given time, Sudan has used its forced return of these individuals as a means of showing support for, as well as disapproval of their home governments. Sudan’s behavior also highlights some shortcomings within the international refugee regime and in certain instances these acts of refoulement represent the Sudanese government’s frustration with this system.